Pengaruh Self-Efficacy terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Matematika - Sukma, Yovika; Priatna, Nanang (Universitas Dr. Soetomo, 2021)
Abstract Critical thinking skills (CTS) is the skill that students require to possess in the 21st century. Research related to students' CTS in Indonesia discusses how students' CTS, including discussing the factors that affect students' CTS. One of the factors that affect students' CTS is self-efficacy. This study will assess the literature using a systematic literature review on whether self-efficacy influences students' CTS. The literature criteria used in this study are the literature in the form of journal articles or conference proceedings indexed by Scopus, Sinta, or Google Scholar with a maximum publication year of the last five years (2017-2021). The purpose of this study is to identify, assess, and make conclusions on the results of research that is relevant to the influence of self-efficacy toward students' CTS in mathematics. Based on the data analysis from the kinds of literature that have met the criteria and through the stage of quality assessment, self-efficacy influences students' CTS in mathematics. Doing this research can provide information about the influence of self-efficacy on the students' CTS and opportunities for research related to self-efficacy and CTS. Keywords: Critical Thinking Skills, Mathematics, Self-Efficacy, Systematic Literature Review Abstrak Kemampuan berpikir kritis atau critical thiking skills (CTS) adalah salah satu kemampuan yang harus dimiliki siswa pada abad 21. Penelitian terkait CTS siswa di Indonesia membahas terkait bagaimana CTS siswa, termasuk membahas tentang faktor-faktor yang mempengaruhi CTS siswa, salah satunya pengaruh dari efikasi diri siswa. Penelitian ini akan mengkaji secara literatur dengan menggunakan systematic literature review terkait apakah efikasi diri mempengaruhi CTS siswa. Kriteria literatur yang digunakan pada penelitian ini yaitu berupa artikel jurnal atau prosiding konferensi yang terindeks Scopus, Sinta, atau Google Scholar dengan tahun publikasi maksimal 5 tahun terakhir (tahun 2017-2021). Tujuan penelitian ini adalah untuk mengidentifikasi, mengkaji, serta membuat kesimpulan dari literatur yang relevan dengan pengaruh efikasi diri terhadap CTS siswa pada mata pelajaran matematika. Berdasarkan hasil analisis data dari literatur yang menjadi data penelitian, efikasi diri mempengaruhi CTS siswa pada mata pelajaran matematika. Dengan dilakukannya penelitian ini dapat memberikan informasi terkait pengaruh efikasi diri terhadap CTS siswa serta peluang untuk melakukan penelitian terkait efikasi diri dan CTS. Kata Kunci: Efikasi Diri, Kemampuan Berpikir Kritis, Matematika, Systematic Literature Review